Facile synthesis of CdS/Bi4V2O11 photocatalysts with enhanced visible-light photocatalytic activity for degradation of organic pollutants in water. Issue 37 (15th September 2017) - Lv, Taotao; Li, Di; Hong, Yuanzhi; Luo, Bifu; Xu, Dongbo; Chen, Min; Shi, Weidong
Abstract : The development of Z-scheme heterojunction photocatalytic systems is a promising strategy to produce hydrogen and for pollutant degradation. Abstract : The development of Z-scheme heterojunction photocatalytic systems is a promising strategy to produce hydrogen and for pollutant degradation. In this study, the direct Z-scheme CdS/Bi4 V2 O11 photocatalysts were synthesized via a two-step solvothermal method. The photocatalytic properties of the samples were measured by ciprofloxacin (CIP), tetracycline (TC) and rhodamine B (RhB) degradation under visible light ( λ > 420 nm). In addition, a probable reaction mechanism for organic pollutants over CdS/Bi4 V2 O11 photocatalysts was also proposed based on the analysis of electron spin resonance (ESR) and active species capture experiments. The enhanced photocatalytic activity of CdS/Bi4 V2 O11 photocatalysts was ascribed to the efficient electron transfer of direct Z-scheme CdS/Bi4 V2 O11 photocatalysts.